Ecotheology, Philosophy, and Literary Narratives: Crossroads of Environmental Ethics - Şencan, Selin (Dialog, 2025)
The main aim of this article is to explore the intersections of ecological theology, philosophy, and literary narratives in the context of environmental ethics. By examining the interplay of theological doctrines, philosophical frameworks, and the imaginative scope of literary storytelling, this article investigates the shared agency between humans and the natural world in addressing ecological crises. In doing so, this article emphasizes the interdependence of spiritual, ethical, and narrative structures, where the environment is not merely a passive backdrop for human-centered moral inquiries. On the contrary, it is presented as an active participant, a dynamic matrix that informs and transforms ethical thought and practice. At the same time, this article argues that integrating theology, philosophy, and literary narratives disrupts the anthropocentric assumption that human agency alone dictates ethical and ecological frameworks, instead advocating for a relational model where human and nonhuman entities co-shape environmental stewardship.